Substitusi Tepung Ubi Jalar Putih (Ipomoea Batatas) dan Penambahan Abon Ayam: Karakteristik Sensori dan Kesukaan Waffle - Nauli, Patricia Paulina; Any Sutiadiningsih; Lilis Sulandari; Ila Huda Puspita Dewi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Waffles are a typical Belgian food. This type of snack is made from a wheat flour-based dough and cooked using a patterned mold. In this chicken floss waffle study, the basic ingredients were substituted with wheat flour, white sweet potato flour, and the addition of chicken floss. This study aimed to determine the effect of the formulation on sensory testing and the level of product preference. The method used was to conduct an experiment substituting 65% wheat flour, 35% white sweet potato flour, and 30% chicken floss. This sensory test was conducted by trained and semi-trained panelists, assisted by distributing observation sheets with a rating of (5-1) and nutritional testing was conducted in the laboratory. Data analysis using the Two Way method, the best data analysis results were found in C3S3 with a substitution of 50% wheat flour, 50% white sweet potato flour, and 40% chicken floss and assisted by organoleptic properties based on color, texture, aroma, taste, color preference, taste preference, color preference, aroma preference, overall preference, has a nutritional content of 52.41% carbohydrates, 8.56% protein, 6.88% fat, 2.31% fiber.